KONFLIK DAN KETEGANGAN DALAM HUKUM ISLAM ANTARA STABILITAS DAN PERUBAHAN - Musyahid, Achmad (Jurusan Syariah dan Ekonomi Islam STAIN Parepare, 2012)
Conflict and tension is by Noel James Coulson in Islamic jurisprudence that the law of God is always confronted with the process of human intellectual activity that tries to transform the law of God. Law is a system of commandments determined divinity. Rejecting the principle is basically leaving the faith in Islam. While the transformation of man-made law take its own shape in the system of rights and obligations. The validity of the theory is not appropriate because Coulson puts clerical dissent as a form of conflict and contradiction in the law of Islam, although in epistimologi Islamic law that is intended to understand and find the law is not to define or create it. In the social history of Islamic law distinction paradigms of legal thought, especially among ahl rayi and Ahl- Hadith is not something that reflects the nature of the conflict and discord among Islamic jurists but the difference is the difference in viewing epistimologi Islamic law